2019
DOI: 10.1002/jpen.1697
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Administration of a Complex Lipid Emulsion Supplement Prevents Postnatal Deficits in Docosahexaenoic and Arachidonic Acids and Increases Tissue Accretion of Lipophilic Nutrients in Preterm Piglets

Abstract: Background: Preterm delivery and current nutrition strategies result in deficiencies of critical long-chain fatty acids (FAs) and lipophilic nutrients, increasing the risk of preterm morbidities. We sought to determine the efficacy of preventing postnatal deficits in FAs and lipophilic nutrients using an enteral concentrated lipid supplement in preterm piglets. Methods: Preterm piglets were fed a baseline diet devoid of arachidonic acid (AA) and docosahexaenoic acid (DHA) and randomized to enteral supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…In a preterm piglet model evaluating the effect of an enteral complex lipid emulsion containing LCPUFAs on early postnatal fatty acid levels, it was demonstrated that an ARA:DHA ratio >1.0 compared to a ratio <1.0 uniquely prevented the postnatal deficit of ARA while also demonstrating increased ileal villus height and muscular thickness compared to the control soybean-oil and ARA:DHA <1.0 groups [54]. In contrast, parenteral nutrition did not show an effect on intestinal morphology and function in preterm piglet models, suggesting postnatal intestinal adaptation is driven more by enterally administered fatty acids versus parenteral delivery [55].…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…In a preterm piglet model evaluating the effect of an enteral complex lipid emulsion containing LCPUFAs on early postnatal fatty acid levels, it was demonstrated that an ARA:DHA ratio >1.0 compared to a ratio <1.0 uniquely prevented the postnatal deficit of ARA while also demonstrating increased ileal villus height and muscular thickness compared to the control soybean-oil and ARA:DHA <1.0 groups [54]. In contrast, parenteral nutrition did not show an effect on intestinal morphology and function in preterm piglet models, suggesting postnatal intestinal adaptation is driven more by enterally administered fatty acids versus parenteral delivery [55].…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…The recent ImNuT (Immature, Nutrition Therapy) trial, also enterally supplementing preterm infants with AA:DHA at 100:50 mg/kg/day, reported a small increase in the molar percent of whole blood DHA between day 2 and PMA 36 weeks but no significant effect on AA levels [ 20 ]. In both this and the ImNuT trial, the supplement was provided as pure oil, and emulsification of the fat would likely have enhanced the LCPUFA bioavailability, as demonstrated in both experimental and clinical studies [ 35 , 36 ]. Increased supplement dosing and/or improved lipid delivery may be needed to avoid infant LCPUFA shortfall.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining birth levels of AA is critical to neonatal development, as a postnatal decrease in AA has been associated with increased risk of neonatal morbidities such as late-onset sepsis and retinopathy of prematurity [ 4 , 13 ]. We have previously shown in a pig model that providing enteral lipid emulsions with an AA:DHA ratio > 1 maintained birth levels of AA and improved intestinal development in preterm pigs [ 39 ]. Together, these data suggest that it is not only individual fatty acids such as AA and DHA, but the ratio of these fatty acids are crucial for neonatal development.…”
Section: Discussionmentioning
confidence: 99%